Analisis Dampak Penanaman Modal Asing Dan Tenaga Kerja Asing Tiongkok terhadap Perekonomian Indonesia - Neli Aida; ukhti Ciptawaty; Toto Gunarto; Syarifah Aini (Jurnal Ekonomi Pembangunan, 2021)
This study will discuss the influence of the influx of foreign investment and Chinese foreign workers on the Indonesian economy, where cooperation between the two countries uses a turnkey project scheme. This study uses secondary data with time-series data types and is sourced from the Central Statistics Agency, the Investment Coordinating Board, and the Ministry of Manpower for the 2010-2019 period. The method used in this research is quantitative and statistical descriptive using multiple linear regression or OLS (Ordinary Least Square). The study results show a positive influence of Chinese foreign investment on the Indonesian economy and Chinese foreign workers who positively impact the Indonesian economy. Although both are below 1 percent, the percentage of Chinese foreign workers' influence on the Indonesian economy is greater than that of Chinese foreign investment.